LEGAL PROTECTION FOR LENDERS IN THE EVENT OF FAILURE OF CREDIT INSURANCE CLAIMS ON PEER TO PEER LENDING PLATFORMS - Galuh Prima Ningrum; Duhita Driyah Suprapti (Universitas Negeri Semarang, 2026)
The development of Peer to Peer (P2P) Lending services as part of Information Technology-Based Joint Funding Services (LPBBTI) provides promising investment opportunities, but also contains significant default risks for lenders. In practice, risk mitigation mechanisms through credit insurance are not always effective, especially when claims cannot be realized due to the absence or unclearness of an active policy, thus creating legal uncertainty and weakening the lender's position. This study aims to analyze the lender's legal position in the policy as well as the responsibility of the organizer for the failure of credit insurance claims. This research uses normative legal methods with a statutory and conceptual approach, and is supported by literature studies through relevant primary and secondary legal materials. The results of the study show that the failure of claims is caused by the expiration of the policy agreement and the lack of transparency of information to the lender, which can be qualified as default, unlawful acts, and consumer protection violations. In addition, there is confusion regarding the position of the lender as the aggrieved party when there is a default in making insurance claims, thus limiting the lender's access to insurance protection. This study concludes that the implementation of legal protection for lenders is not optimal, so it is necessary to strengthen supervision, increase transparency, and reconstruct legal relationships in credit insurance schemes to ensure legal certainty and more effective protection for lenders.